Pour l’histoire des relations internationales - Saraiva, José Flávio Sombra; Coelho, Natália Bandeira Ramos; Notari, Maria Helena Helena de Aguiar (Meridiano 47 - Journal of Global Studies, 2017)
Resenha da obra: FRANK, Robert. Pour l’histoire des relations internationales. Paris: PUF, 2012. ISBN : 978-2-13-060624-6